Understanding the Immune and Inflammatory Response to Rhinoviruses: Recent Advances with Relevance to Asthma - Kunarajah, Kuhan; Pena, Olga; W. Upham, John (Current Respiratory Medicine Reviews, 2016)
Human rhinoviruses (HRVs) are responsible for most cases of the common cold. In healthy people, the consequences of HRV infections are usually minor. However, this innocuous virus can have serious consequences in certain individuals, with HRV infections linked to the onset of asthma in young children, and to potentially life threatening exacerbations in those with established asthma. Understanding the pathogenesis of HRV infections in asthma is thus a subject of much interest. This article reviews recent advances in our understanding of HRV-induced inflammatory pathways and immune responses, focussing on publications from the last 4 years. We outline new insights into the different types of HRVs, the cellular receptors they engage, and the transcriptional pathways that are engaged as a prelude to interferon synthesis. The importance of cross-talk between the innate immune response to HRV infections and cytokines produced during allergic inflammation is emphasised, with researchers continuing to document both altered anti-viral interferon production and immune dysregulation in asthma. Better definition of the mechanisms by which HRV infections induces lower airway inflammation is an important foundation on which to develop novel therapies that target HRV and/or the immunopathology that it induces.
Keywords: rhinovirus